2021
DOI: 10.17159/2078-516x/2021/v33i1a10651
|View full text |Cite
|
Sign up to set email alerts
|

No time to waste: necessary health support for retired professional rugby players

Abstract: There has been increasing scrutiny of professional rugby following the concern that retired players might face several negative health conditions. Currently, support measures addressing the health of retired professional rugby players are not systematically implemented. This is unusual as professional rugby stakeholders have the duty of care to protect and promote the long-term health of retired players. Professional football has a health programme for retired players that is implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…As a result, former elite rugby players require unique and thorough support during their retirement years. One of the support measures which was developed to improve the quality of life and long-term health of former professional male and female rugby players is the After Rugby Career Consultation (ARCC) 48. The ARCC was developed based on scientific evidence and according to the needs of active and retired players, to be implemented as a transitioning health examination for retired elite rugby players.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, former elite rugby players require unique and thorough support during their retirement years. One of the support measures which was developed to improve the quality of life and long-term health of former professional male and female rugby players is the After Rugby Career Consultation (ARCC) 48. The ARCC was developed based on scientific evidence and according to the needs of active and retired players, to be implemented as a transitioning health examination for retired elite rugby players.…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach has been implemented globally in professional football. A number of key stakeholders in South African rugby, including the South African Rugby Union, MyPlayers and the South African Rugby Legends Association, have allied to trial the ARCC within the context of South African rugby 48…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, our results confirmed that mental suffering is prevalent in gymnastics; 90.9% of participating gymnasts declared being stressed, and more than 50% described symptoms like sadness and anxiety. Consequently, it is essential to screen gymnasts for mental health and manage them appropriately, as well as to prevent mental health problems in WAG [16,18,19].…”
Section: Injury Risk Factorsmentioning
confidence: 99%
“…It justifies the need to continue their understanding by extending this research to other risk factors, such as lifestyle (e.g., sleep, nutrition, school, and daily organization) and mental health, which can play a role on injuries [14][15][16]. Indeed, injuries can impact mental health and quality of life and could have long-term effects physically as well as psychologically and vice versa [15,[17][18][19]. Palmer et al [20] reported that the prevalence of depression reached 6.6% in Olympic athletes during their careers.…”
Section: Introductionmentioning
confidence: 99%